THE EFFECT OF HIGH TEMPERATURE ON SERUM ELECTROLYTES AND TRACE ELEMENTS FOR EMPLOYEES OF FURNACE IN RAMADI GLASS FACTORY - SAFA K. Al-AMIN; MAHMOOD M.ATEA; MOHAMMED Q. AL-ANI; ABED A. THAKER (مجلة جامعة الانبار للعلوم الصرفة, 2012)
This study includes determination of the effect of high temperature on the serum electrolytes and trace elements in thirty workers of furnace in Ramadi glass factory (Anbar – Iraq). Thirty technicians and administrators for interior control and thirty volunteers as external control. From the results of this study we observed that: K and P decreased significantly (P< 0.01), Mg remained within the normal value,Fe increased significantly (p<0.01) and Cu decreased significantly (P < 0.01) , Zn/Cu ratio increased significantly (P < 0.01) . In conclusion, this study indicates that: the exposure to high temperature causes changes in the compositions of some constituents of blood.